The Effect of Methyl and Chloro Substituent Compounds in Amida Derivatives Synthesis from p-Metoxicynamic Acid with Microwaves Irradiation - Ruri Intan Nurcahyaningtyas; Juni Ekowati Ekowati; Marcellino Rudyanto (Universitas Airlangga, 2020)
Background: The difference in the nature of these aromatic amine substituents, i.e. methyl and chloro will affect the N atom of aniline as a nucleophile to attack the carbonyl C atom in the p-methoxcycinnamoyl chloride in the synthesis two amides derivate of p-methoxycinnamic acid, namely N-(p-methylphenyl)-p-methoxycinnamide and N-(p-chlorophenyl)-p-methoxycinnamide. Aim: to obtain the N-(p-methylphenyl)-p-methoxycinnamide and the N-(p-chlorophenyl)-p-metoxicinamide compound from p-methoxycinamic acid using the microwave irradiation method as source of energy. Beside that, it also to determine the effect of the presence of methyl and chloro substituents in para position of aromatic amines in the yields of reactions. Method: The reactions were carried out by microwave irradiation at three powers, i.e 120 watts, 200 watts, 280 watts. After separation and purification steps, the products were identified by spectrometric methods. Result: At power of 200 watts for reaction time of 7.5 minutes, the yield of N-(p-methylphenyl)-p-methoxycinamide is larger than N-(p-chlorophenyl)-p-methoxycinnamamide. The percentage of the product synthesis of N-(p-methylphenyl)-p-methoxycinamide was 51.84% and the percentage of N-(p-chlorophenyl)-p-methoxycinnamamide was to 47.20%. Conclusion: The effect of substituent methyl is increase the percentage yield of N-(p-methylphenyl)-p-methoxycinamide compound than that substituent chloro of N-(p-chlorophenyl)-p-methoxycinamide compound under the same reaction conditions. Based on the identification of the structure of the synthesized compound using a UV spectrophotometer, infrared spectrophotomers and 1H-NMR spectrometer it can be concluded that the synthesized compounds are N-(p-methylphenyl)-p-methoxycinnamide and N- (p-chlorophenyl)-p-methoxycinnamide.